2017
DOI: 10.1007/s00417-017-3715-9
|View full text |Cite
|
Sign up to set email alerts
|

OCT in Alzheimer’s disease: thinning of the RNFL and superior hemiretina

Abstract: Patients with AD showed a significant thickness reduction in global and temporal superior quadrants in pRNFL and in superior pericentral and peripheral sectors of RT. These findings may reflect a peripapillary and retinal changes characteristic of AD, suggesting the importance of SD-OCT as a potential adjuvant in early diagnosis of AD. Further studies are needed to understand which retinal layers and macular sectors are more useful as potential ocular biomarker over time in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 40 publications
4
73
1
Order By: Relevance
“…[13] provided histopathological evidence of optic neuropathy and degeneration of retinal ganglion cells in AD subjects, and later, in a postmortem study, substantial GCL degeneration was demonstrated in the foveal/parafoveal region in AD. OCT imaging in vivo first showed decreased total macular thickness in AD subjects [16,31] and later, when macular segmentation was available, Marziani et al. reported significant reductions in combined RNFL and GCL thickness (RNFL+GCL+IPL) in the macular region [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] provided histopathological evidence of optic neuropathy and degeneration of retinal ganglion cells in AD subjects, and later, in a postmortem study, substantial GCL degeneration was demonstrated in the foveal/parafoveal region in AD. OCT imaging in vivo first showed decreased total macular thickness in AD subjects [16,31] and later, when macular segmentation was available, Marziani et al. reported significant reductions in combined RNFL and GCL thickness (RNFL+GCL+IPL) in the macular region [15].…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, Hinton et al [13] provided histopathological evidence of optic neuropathy and degeneration of retinal ganglion cells in AD subjects, and later, in a postmortem study, substantial GCL degeneration was demonstrated in the foveal/ parafoveal region in AD. OCT imaging in vivo first showed decreased total macular thickness in AD subjects [16,31] and later, when macular segmentation was available, Marziani et al reported significant reductions in combined RNFL and GCL thickness (RNFL1GCL1IPL) in the macular region [15]. Nevertheless, Cheung et al [33] suggested that including the RNFL in the GCL analysis in the macular area may influence the sensitivity for revealing GCL abnormalities, so they measured GCL-IPL without including the RNFL and found significant GCL-IPL thinning in AD and MCI patients compared with HC.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, evidence of total macular thickness decreased in patients with AD was demonstrated with time domain OCT (TD-OCT) [ 53 ] and stratus OCT [ 49 , 54 ]. Subsequently, it was confirmed by several independent groups using modern OCT devices, such as spectral-domain OCT [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 93%
“…OCT examination reveals a thinner retinal nerve fibre layer in patients with Alzheimer's disease . Retinal nerve fibre layer thickness is reported to be lower overall as well as in all four quadrants in comparison to that of healthy controls.…”
Section: Alzheimer's Diseasementioning
confidence: 93%